PWE-040 Lymph node metastasis in early oesophageal cancer: experience from a 10 year UK cohort. (28th May 2012) - Athwal, T S; Love, S; Bruce, S; Page, R; Hartley, M; Howes, N
Abstract : Introduction: Surgical resection is considered the gold standard curative treatment for oesophageal cancer, however, there is debate regarding the role of endoscopic resection for "early" (Tis, T1) oesophageal cancer. However, studies have identified that a significant number of early cancers will have lymph node metastases (LNM) at time of diagnosis. The aim of this study was to determine the incidence of LNM in early oesophageal cancer patients in a 10 year UK cohort. Methods: A total of 482 consecutive patients who had transthoracic oesophagectomy for adenocarcinoma or squamous cell carcinoma, at a supra-regional upper GI cancer centre, were registered on a prospective database between 2002 and 2012. Patients with early oesophageal cancer were retrieved from the database based on pre-operative endoscopic and radiological staging. Results: Of the 482 patients, 53 (11%) had early oesophageal cancer, of which 41 (77%) were adenocarcinoma, 11 (21%) squamous cell carcinoma and 1 (2%) carcinoma in situ. The median lymph node harvest was 14 (IQR 9–17). Lymph node metastases were present in 4 (7.6%) cases, all of which had tumour extending into the submucosal layer. Conclusion: Early oesophageal cancer has a significant risk of lymph node involvement especially when the submucosal layer is breached by tumour. In our opinion, surgical resection remains the gold standard to achieve cure in patients with early cancer. Competing interests: None declared.